Health services management in primary schools (Elazig city sample) - Arabaci, I. Bakir (Elsevier Science Bv, 2009)
Primary school children have low resistance to diseases. In order to live a healthy life, they should be equipped with health literacy skills. Effective primary school health services can only be achieved with the collaboration of related parties. Turkish schools generally do not employ permanent health personnel, and school health services are generally taken to be synonymous with health screening. This study is a descriptive survey using the School Health Services Scale designed by the presenter. The results show that participants have a positive perception of school health services. At the same time, being male, being an administrator, attending a private school, a county school or a school with a nurse and sickroom were found to create a meaningful difference in the perception of health services. Also, the dimension of creating a healthy environment at school was found to be predictive of developing a health culture. (c) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: Primary schools; school health services; healthy environment; health culture